Phylogeography and Genetic Diversity of Francisella tularensis subsp. holarctica in France (1947–2018) - Kevin, Maëllys; Girault, Guillaume; Caspar, Yvan; Cherfa, Moulay Ali; Mendy, Christiane; Tomaso, Herbert; Gavier-Widen, Dolores; Escudero, Raquel; Maurin, Max; Durand, Benoît; Ponsart, Claire; Madani, Nora (Frontiers in Microbiology, 2020)
In France, tularemia is caused by Francisella tularensis subsp. holarctica and is a sporadic disease affecting mainly wildlife animals and humans. F. tularensis species presents low genetic diversity that remains poorly described in France, as only a few genomes of isolates from the country are available so far. The objective of this study was to characterize the genetic diversity of F. tularensis in France and describe the phylogenetic distribution of isolates through whole-genome sequencing and molecular typing. Whole genomes of 350 strains of human or animal origin, collected from 1947 to 2018 in France and neighboring countries, were sequenced. A preliminary classification using the established canonical single nucleotide polymorphism (canSNP) nomenclature was performed. All isolates from France (except four) belonged to clade B.44, previously described in Western Europe. To increase the resolution power, a whole-genome SNP analysis was carried out. We were able to accurately reconstruct the population structure according to the global phylogenetic framework, and highlight numerous novel subclades. Whole-genome SNP analysis identified 87 new canSNPs specific to these subclades, among which 82 belonged to clade B.44. Identifying genomic features that are specific to sublineages is highly relevant in epidemiology and public health. We highlighted a large number of clusters among a single clade (B.44), which shows for the first time some genetic diversity among F. tularensis isolates from France, and the star phylogeny observed in clade B.44-subclades revealed that F. tularensis biodiversity in the country is relatively recent and resulted from clonal expansion of a single population. No association between clades and hosts or clinical forms of the disease was detected, but spatiotemporal clusters were identified for the first time in France. This is consistent with the hypothesis of persistence of F. tularensis strains found in Western Europe in the environment, associated with slow replication rates. Moreover, the presence of identical genotypes across long periods of time, and across long distances, supports this hypothesis but also suggests long-distance dispersal of the bacterium.